ACCURACY ORDER OF THE GRAMMATICAL MORPHEMES IN THE ORAL PRODUCTION OF PRESCHOOL PUPILS - Barrot, Jessie; de Leon, Kristine (Universitas Pendidikan Indonesia, 2014)
Abstract. There are numerous studies concerning the order of acquisition of grammatical morphemes; however, no paper to the knowledge of the authors has explored the accuracy order and acquisition of grammatical morphemes of Filipino children. The present study investigated the accuracy order of 14 English grammatical morphemes of Filipino preschool pupils. Specifically, this paper sought to determine the grammatical morphemes which have the highest and lowest accuracy level by Filipino preschool pupils. It also attempted to identify whether there is a relationship between the order of grammatical morpheme acquisition of Filipino preschool pupils compared to the order of grammatical morpheme wherein English is the first language and English is the second language. The participants involved in this study were 18 preschool pupils whose age ranges from three to five years old. These participants were divided into two clusters based on their linguistic and geographical background. The findings revealed that plurality and progressive verbs posted the highest accuracy level while prepositions and past irregular verbs had the lowest level of accuracy. As regards the relationship between the order of acquisition, the results revealed that the present study posted a different order compared to Dulay and Burt’s (1973) and Brown’s (1973) studies through Kendall coefficient of concordance and Spearman Rank Order Correlation. Keywords: Accuracy order, L2 acquisition, order of acquisition, grammatical morphemes KEAKURATAN URUTAN MORFEM TATA BAHASA DALAM PRODUKSI LISAN SISWA PRA-SEKOLAHAbstrak: Ada banyak kajian mengenai urutan pemerolehan morfem-morfem tata bahasa, akan tetapi sepengetahuan penulis tidak ada makalah yang telah menggali keakuratan urutan dan pemerolehan morfem tata bahasa diantara anak-anak Filipina. Kajian ini menyelidiki keakuratan urutan dari empat belas morfem tata bahasa Inggris diantara siswa pra-sekolah Filipina. Khususnya, makalah ini berusaha untuk menentukan morfem-morfem tata bahasa yang memiliki tingkat keakuratan tertinggi dan terendah diantara siswa pra-sekolah Filipina. Kajian ini juga berusaha untuk melihat apakah ada hubungan antara urutan pemerolehan morfem tata bahasa para siswa pra-sekolah Filipina dengan urutan morfem tata bahasa dimana Inggris sebagai bahasa pertama dan kedua. Para peserta yang terlibat dalam kajian ini adalah 18 siswa pra-sekolah yang berumur antara tiga sampai lima tahun. Para peserta ini dibagi ke dalam dua kelompok berdasarkan latar belakang bahasa dan geografisnya. Temuan-temuan menunjukkan bahwa kata-kata kerja jamak dan progresif (sedang berlangsung) memiliki keakuratan paling tinggi, sementara kata depan dan kata-kata kerja tidak beraturan lampau memiliki keakuratan yang paling rendah. Mengenai hubungan antara urutan pemerolehan, hasilnya mengungkapkan bahwa kajian ini menunjukkan urutan yang berbeda dibanding dengan hasil kajian Dulay dan Burt (1973) serta Brown (1973) melalui koefisien keselaran (coefficient of concordance) Kendall dan Korelasi Urutan Ranking (Rank Order Correlation) Spearman. Katakunci: Keakuratan urutan, pemerolehan bahasa kedua, urutan pemerolehan, morfem tata bahasa